ANALISIS FRAMING PEMBERITAAN KASUS REYNHARD SINAGA (STUDI KOMPARATIF MEDIA ONLINE BBC.COM INDONESIA DAN KOMPAS.COM) - Wulan Shonya Saputri; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Mass media coverage in early 2020 was enlivened by news of cases of rape and sexual assault against men by Reynhard Sinaga in Manchester, England. This case has quickly caught the attention of the public since the news was published on January 6, 2020. This research focuses on the analysis of differences in news framing conducted by the online media BBC.com Indonesia and Kompas.com. The purpose of this research is to identify and describe the framing of the news presented by BBC.com Indonesia and Kompas.com by using the social media reality construction theory.This study used a qualitative approach with the Zhongdang Pan and Gerald M. Kosicki framing analysis. The object of this research is the text of the Reynhard Sinaga case news on BBC.com Indonesia and Kompas.com which are selected based on news published on the same day, and have relevant titles, topics and headlines between BBC.com Indonesia and Kompas.com. The selected news ranges from January 6, 2020 - January 9, 2020. The data collection techniques used in this study were observation, documentation and literature study.The results showed that the online media BBC.com Indonesia, as the media that first focused on the Reynhard Sinaga case, generally has a frame that tends to view the news of the Reynhard Sinaga case as the biggest case of sexual violence in British history. The way BBC.com Indonesia presents the facts of this case seems very open and independent, it can be seen from the explicit statements that are often found in the news texts. The source presented by BBC.com Indonesia is also felt to be supportive in emphasizing the facts of the Reynhard case as the biggest rape case in British history. Meanwhile, Kompas.com saw this incident as an important opportunity to report this case to the public, considering that this case was quite surprising and attracted the attention of many parties. The use of language and writing information in Reynhard Sinaga's news is packaged straightforwardly and carefully. Kompas.com, in its reporting, tries to be as objective as possible in presenting facts related to the Reynhard case, by releasing data from international online media such as The Guardian and the BBC.Keywords : Framing, News, Construction, Reynhard Sinaga